PENGEMBANGAN MEDIA PEMBELAJARAN TEKAGA BERBASIS CONSTRUT 2 MUPEL IPAS KELAS IV SDN BUTUH 1 SAWANGAN - Ahmad Bagus Fernanda; Farid Ahmadi (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
This study discussed the learning media in the form of TEKAGA (Tebak Kata Gambar) based on Construct 2 class IV SD science content material Indonesia Rich and Culture. The research is Research and Development (R & D). The Steps of this research used the Borg and Gall model, which were adjusted to the development needs, time, and circumtances of the research, including potential and problems, collection of data/information, product design, design validation, revised Design small-class product trials, revise products, large-class trials. The software development method used the Multimedia Development Life Cycle or we are often familiar MDLC method. The research a instructional media that can be accessed via a smartphone or computer using Construct 2, which is based on HTML 5 to develop games.